Enzymatic peeling: first advance on the development of the flavor sensory profile of Navel oranges - Pieroni, Victoria Andrea (2021)
Enzymatic peeling is one of the methods used to obtain minimally processed citrus fruit. The present work has studied the effect of enzymatic peeling produced on the flavor sensory profile of different cultivars of navel oranges. A trained panel conducted a descriptive analysis. The following flavor descriptors were defined and evaluated: bitter, sweet, acid, orange, and fermented. The enzymatic treatment has influenced the three orange cultivars studied in different manners. In Navelina cultivar, this treatment affected negatively, intensifying bitterness and fermented flavor, so it would not be a recommended cultivar to be minimally processed. Lane late cultivar was affected by enzymatic treatment in sweetness and orange flavor descriptors, decreasing their intensity. In the Parent cultivar, the peeling treatment has not affected the flavor of oranges as this cultivar of oranges remains as one of the sweetest and most orange-flavored ones.